Apakah Pengeluaran Pemerintah Mempengaruhi Kemiskinan, Kesehatan, dan Pendidikan? Studi Kasus Provinsi Aceh, Indonesia - Arifka Yusri (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
Economists have talked about government expenditure and its relation to poverty, health, and education for decades. Indeed, many theories and empirical evidence have been conducted since then. This study evaluates the relationship between Special Autonomy Fund (SAF) and poverty, health, and education indicators in Aceh province, Indonesia, using a panel dataset of 30 regions in the 2002-2018 period. Synthetic Control Method (SCM) is used as the model to accommodate the allocation of SAF to Aceh given by the central government since it is commonly applied to the cases of policy intervention in comparative case studies. This paper discovers that the SAF plays a vital role in lowering the poverty rate, escalating access to safe sanitation, and improving the net enrollment ratio of senior secondary schools. However, there is no prominent association between SAF allocation and access to safe water. This outcome variable shows positive and negative signs; therefore, a conclusion could not be provided.